Penguatan Mutu Sekolah Melalui Kolaborasi Pendampingan Rintisan Sekolah Swasta Gratis (RSSG) di Kota Depok - Yasnita, Yasnita; Dadang Wihana; Fathir Fajar Sidiq; Siti Chaerijah Aurijah; Destiana Rachmawati; Yusuf, Muhammad; Sugihartono, Iwan; Raharjo, Raharjo; Widyaningrum Indrasari; Rafiudin, Rafiudin; Setiawan, Iwan (Bahasa Indonesia, 2025)
The Free Private School Pilot Program (RSSG) is an innovative policy by the Depok City Government to expand access to education for low-income families through partnerships with private schools. Initial findings show that the quality of RSSG schools in Depok City varies greatly. Of the 47 participating schools spread across 11 subdistricts, 20 schools are accredited A, 23 are accredited B, two are accredited C, and two are not yet accredited. The total number of students reaches 2,407. The variation in accreditation and infrastructure shows a gap in quality between schools, which is the basis for the implementation of mentoring. Therefore, it is necessary to strengthen school quality through RSSG mentoring collaboration. Jakarta State University is the institution entrusted with carrying out community service activities through mentoring teachers and school principals. These community service activities are carried out by lecturers and students of Jakarta State University (UNJ) as part of efforts to strengthen the quality and sustainability of the program. The community service activities focused on two main areas: (1) mentoring teachers in 47 RSSG schools through four cycles of thematic training on strengthening understanding of student characteristics, implementing deep learning, active learning models, and creating simple learning media; and (2) training school principals at Depok City Hall on the theme of “Strengthening School Branding and Culture,” which was attended by 47 school principals. The results of the activities showed an increase in teachers' knowledge and capacity in designing meaningful, contextual, and relevant learning for students' needs, as well as the growth of school principals' awareness in building a positive institutional identity and culture. This program not only improved the technical quality of learning but also strengthened the collaborative ecosystem that supports educational equity in Depok City.   Abstrak Program Rintisan Sekolah Swasta Gratis (RSSG) merupakan inovasi kebijakan Pemerintah Kota Depok dalam memperluas akses pendidikan bagi keluarga berpenghasilan rendah melalui kemitraan dengan sekolah swasta. Hasil kajian awal menunjukkan bahwa mutu sekolah RSSG di Kota Depok sangat beragam. Dari 47 sekolah pelaksana yang tersebar di 11 kecamatan, tercatat 20 sekolah berakreditasi A, 23 berakreditasi B, dua berakreditasi C, dan dua belum terakreditasi. Total peserta didik mencapai 2.407 siswa. Variasi akreditasi dan sarana prasarana menunjukkan adanya kesenjangan mutu antar sekolah, yang menjadi dasar pelaksanaan pendampingan. Untuk itu, maka perlu dilakukan upaya penguatan mutu sekolah melalui kolaborasi pendampingan RSSG. Universitas Negeri Jakarta menjadi institusi yang diberi kepercayaan untuk melakukan kegiatan pengabdian masyarakat melalui kegiatan pendampingan guru dan kepala sekolah. Kegiatan pengabdian masyarakat ini dilaksanakan oleh dosen dan mahasiswa Universitas Negeri Jakarta (UNJ) sebagai bagian dari upaya memperkuat kualitas dan keberlanjutan program. Kegiatan pengabdian meliputi dua fokus utama: (1) pendampingan guru di 47 sekolah RSSG melalui empat siklus pelatihan tematik penguatan pemahaman karakteristik siswa, implementasi deep learning, model pembelajaran aktif, dan pembuatan media pembelajaran sederhana; serta (2) pelatihan kepala sekolah di Balai Kota Depok bertema “Penguatan Branding dan Budaya Sekolah” yang diikuti oleh 47 kepala sekolah, Hasil kegiatan menunjukkan peningkatan pengetahuan dan kapasitas guru dalam mendesain pembelajaran bermakna, kontekstual dan relevan dengan kebutuhan siswa, serta tumbuhnya kesadaran kepala sekolah dalam membangun identitas dan budaya positif lembaga. Program ini tidak hanya memperbaiki mutu teknis pembelajaran, tetapi juga memperkuat ekosistem kolaboratif yang mendukung keadilan pendidikan di Kota Depok.